Integrated microbiome and metabolome analysis reveals the potential therapeutic mechanism of Qing-Fei-Pai-Du decoction in mice with coronavirus-induced pneumonia - Wu, Gaosong; Zhang, Wendan; Zheng, Ningning; Zu, Xianpeng; Tian, Saisai; Zhong, Jing; Zhang, Yuhao; Liao, Jingyu; Sheng, Lili; Ge, Guanbo; Li, Houkai; Zhang, Weidong (Frontiers in Cellular and Infection Microbiology, 2022)
Current studies have shown that gut microbiota may be closely related to the severity of COVID-19 by regulating host immune response. Qing-Fei-Pai-Du decoction (QFPDD) is the recommended drug for clinical treatment of patients with COVID-19 in China, but whether it exerts a therapeutic effect by modulating immune response through gut microbiota remains unclear. In the study, we evaluated the therapeutic effects of QFPDD in pneumonia model mice and performed 16S rRNA sequencing, serum and lung tissue metabolomics analysis to explore the underlying mechanisms during the treatment. Then, Spearman correlation analysis was performed on gut microbiome, serum metabolome and immune-inflammation-related indicators. Our results suggest that QFPDD can restore the richness and diversity of gut microbiota, as well as multiple gut microbiota (including Alistipes, Odoribacter, Staphylococcus, Lachnospiraceae_NK4A136_group Enterorhabdus, and unclassified_f_Lachnospiraceae) are significantly associated with immune-inflammation-related indicators. In addition, various types of lipid metabolism changes were observed in serum and lung tissue metabolome, especially glycerophospholipids and fatty acids, a total of 27 differential metabolites (DMs) were significantly correlation with immune-inflammation-related indicators, including 9 glycerophospholipids, 7 fatty acids, 3 lineolic acid, 2 eicosanoids, 2 amino acids, 2 bile acids and 2 others. Interestingly, these DMs showed a good correlation with the gut microbiota affected by QFPDD. The above results suggest that QFPDD can improve the immune function and reduce inflammation in pneumonia model mice by remodeling gut microbiota and host metabolism.